POLA KOMUNIKASI MASYARAKAT MUSLIM MELAYU DAN TIONGHOA: Studi Terhadap Penyelesaian Konflik di Kota Tanjung Balai - Agus Susanto (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This article is the result of research that discusses how sociology of communication plays a role in communication between Malay-Chinese culture so as to minimize misconceptions that are vulnerable to conflict in society. How are the factors causing conflict between Malay and Chinese People in Tanjung Balai City. This research is a qualitative research with sociological-anthropological and phenomenological approach. The results of this study revealed that, to prevent the recurrence of the case of Tanjung Balai, North Sumatra, the people of Indonesia are divided due to socio-economic segregation, shelter, religion, ethnicity, work, there must be hard efforts. the pattern of communication is done with a policy that gives special treatment and affirmative action against the weak especially the natives. In addition, a forum is formed as a forum for dialogue and communication between different groups of socioeconomic stratification, residence, ethnicity, ethnicity and so on. To end social tensions due to socio-economic disparities between ethnic Chinese and indigenous peoples. Factors supporting the Malay and Chinese peace in Tanjung Balai, namely Tanjung Balai community awareness to stop conflict, cooperation of various parties in realizing peace, and the role of security forces in maintaining post-conflict stability. Efforts to stop open conflict and acts of violence that support the success of the negotiations, was successfully carried out by the authorities